Memetics as the new interdisciplinary science and the branch of social semiotics - Shcherbin, Vyacheslav K. (Journal of the Belarusian State University. Sociology, 2020)
The process of formation of a new interdisciplinary science – memetics, which studies historical, cultural, political, social, economic and other types of memes is considered in the article. The interconnections between memetics and social semiotics are analyzed. The conclusion is substantiated that memetics is becoming the branch of social semiotics which relates to different branches of semiotic research (biosemiotics, cybersemiotics, political semiotics, semiotics of culture, economic semiotics, etc.).
Keywords: mem; memetics; social science; classification of memes; social semiotics